2022
DOI: 10.1093/eurheartj/ehac307
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of culture-negative vs. culture-positive infective endocarditis: the ESC-EORP EURO-ENDO registry

Abstract: Aim Fatality of infective endocarditis (IE) is high worldwide, and its diagnosis remains a challenge. The objective of the present study was to compare the clinical characteristics and outcomes of patients with culture-positive (CPIE) vs. culture-negative IE (CNIE). Methods and results This was an ancillary analysis of the ESC-EORP EURO-ENDO registry. Overall, 3113 patients who were diagnosed with IE during the study period w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 22 publications
(43 reference statements)
3
24
4
Order By: Relevance
“…In Spain the results of hospital-based cohorts show much lower proportions of culture-negative endocarditis with figures ranging 10–20% [ 31 , 34 , 50 ]. In a recent study conducted among 3113 IE patients admitted to hospitals in Europe, from January 2016 to March 2019, a positive culture was obtained in 83.2%, whereas 16.8% had a culture-negative [ 51 ]. However, this very high rates are expected because in most hospitalized cohorts of patients with IE, cases were identified by the attending clinician and a high culture-positive rate in these cohorts may therefore reflect selection bias toward patients with positive blood cultures [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Spain the results of hospital-based cohorts show much lower proportions of culture-negative endocarditis with figures ranging 10–20% [ 31 , 34 , 50 ]. In a recent study conducted among 3113 IE patients admitted to hospitals in Europe, from January 2016 to March 2019, a positive culture was obtained in 83.2%, whereas 16.8% had a culture-negative [ 51 ]. However, this very high rates are expected because in most hospitalized cohorts of patients with IE, cases were identified by the attending clinician and a high culture-positive rate in these cohorts may therefore reflect selection bias toward patients with positive blood cultures [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cultures are negative in IE for three major reasons: previous administration of antimicrobial agents, inadequate microbiological techniques, infection with highly fastidious bacteria or nonbacterial pathogens [ 4 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, heart failure and heart murmur were observed more in culture-negative endocarditis patients. 9 …”
Section: Introductionmentioning
confidence: 99%
“…In a recent analysis of the large ESC-EORP EURO-ENDO registry, out of 3113 with IE, 523 patients had CNIE (17%). Overall, CNIE was independently associated with 1-year mortality (hazard ratio [HR] 1.3 with 95% CI from 1.0 to 1.6, p = 0.02), but this association was not appreciable in the subgroup of patients who underwent surgery [ 8 ]. Notably, in the ESC-EORP EURO-ENDO registry congestive heart failure was more frequent in CNIE than in CPIE patients, as also previously observed by other authors [ 3 , 5 ].…”
mentioning
confidence: 99%
“…Notably, in the ESC-EORP EURO-ENDO registry congestive heart failure was more frequent in CNIE than in CPIE patients, as also previously observed by other authors [ 3 , 5 ]. It has been suggested that this could be related to a delayed recognition of IE in the patients with negative blood cultures, with their severe conditions at diagnosis contraindicating surgery and negatively impacting prognosis [ 8 ]. From this standpoint, variations in the frequency of CNIE patients in whom surgery was contraindicated, together with possible differences in the appropriateness (unverifiable due to the lack of etiological diagnosis) of the antibiotic therapy of CNIE, could explain why a few other studies did not register a worse prognosis in CNIE than in CPIE [ 9 , 10 , 11 ].…”
mentioning
confidence: 99%